Analisis Yuridis Putusan Pengadilan Negeri Padang Pariaman Nomor 18/Pid.Sus-Anak/2018/Pn Pmn Tentang Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Seksual - Ummah, Faizzah Wardatul; Rosnawati, Emy (Indonesian Journal Publisher, 2024)
Sexual violence in Indonesia has increased every year, both for children, adolescents, and adults. So legal protection is needed in the form of providing guarantees for security, tranquility, welfare, peace as a form of legal certainty for children to avoid sexual violence. The purpose of this study is to find out and analyze the decision of the Padang Pariaman District Court Number 18/pid.sus-anak/2018/pn pmn regarding legal protection for children as victims of sexual violence. More about the legal topic of juridical analysis of the decision of the Padang Pariaman District Court Number 18/pid.sus-anak/2018/pn pmn regarding legal protection of children as victims of criminal acts of sexual violence. This research method uses a normative juridical method with a case approach. The results of this study indicate that the author does not agree with the judge's consideration in imposing a sentence on the defendant because he did not pay attention to Law Number 35 of 2014 concerning Child Protection, which states that the minimum sentence is 5 years for perpetrators, while (one half) for child offenders in the Act. – Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. So that if sentenced to 1 year 4 months on the perpetrator is considered unfair to the victim. The analysis of legal materials used is deductive reasoning analysis, namely the preparation using a hypothesis or temporary answer. Meanwhile, this study applies a general to specific pattern.